Green Infrastructure and Citizen Participation in NW Europe. The Process of Change in Städteregion Aachen. - Whitehead, Ian (My University, 2021)
Das Ziel der Studie ist es, das Potenzial von Bürgerbeteiligung als Mechanismus für das Management von Grüner Infrastruktur (GI) in Nordwesteuropa und Europa durch die Auswertung von Fallstudien vor Ort in kontrastierenden geographischen Regionen zu evaluieren, mit einem besonderen Schwerpunkt auf der Städteregion Aachen. In den letzten Jahren ist das Bewusstsein für das Konzept der Grünen Infrastruktur (GI) gewachsen, das darauf abzielt, integrierte Umweltdienstleistungen und nachhaltige Entwicklungsvorteile in einem breiten Spektrum von ökologischen, sozialen und wirtschaftlichen Themen zu liefern. Insbesondere wird die Multifunktionalität von Landschaften als Schlüsseleigenschaft von GI betrachtet. Die zunehmende Anerkennung der Notwendigkeit eines integrierten Ansatzes für GI in Europa spiegelt sich in den Gesetzgebungs- und Politikgestaltungsprozessen der EU wider. Parallel zur EU-Priorisierung strategischer Ansätze für GIs gibt es eine wachsende Verlagerung hin zu sogenannten "Mosaik"- Formen der Governance; partizipative Ansätze, die verschiedene Interessengruppen - einschließlich lokaler Bürgergruppen, gesetzlicher Behörden und Mentoren Organisationen - einbeziehen, die partnerschaftlich zusammenarbeiten, oft auf lokaler Ebene. Zu Vergleichszwecken und um zusätzliche Erkenntnisse zu gewinnen, wurden zu einem späteren Zeitpunkt weitere Fallbeispiele aus Schottland in die Studie aufgenommen.

The aim of this study is to evaluate the potential for citizen participation as a mechanism for management of Green Infrastructure (GI) within NW and Europe through evaluation of case studies on the ground in contrasting geographical regions, but with a particular emphasis on the Aachen City Region, Städteregion Aachen. In recent years there has been a growing awareness of the concept of Green Infrastructure (GI) approaches which aim to deliver integrated environmental services and sustainable development benefits across a broad range of ecological, social and economic themes. Significantly, the multi-functionality of landscapes is considered to be a key attribute of GI, with areas expected to simultaneously provide diverse functions such as biodiversity, food production, soil conservation, water & climate regulation, recreation & tourism, wellbeing and cultural services. This contrasts markedly with previous sectorial approaches to landscape management which tended to focus upon single issues such as nature protection, food production or recreation. The growing acknowledgement of the requirement for an integrated approach to GI in Europe is reflected within the EU legislative and policymaking processes. Significant drivers for this, have included global climate change, biodiversity loss and sustainable development policies at national, European and global scale. Parallel to the EU prioritisation of strategic approaches to GI, is the growing shift towards so-called “mosaic” forms of governance; participatory approaches which involve diverse stakeholders - including local citizens groups, statutory authorities and mentoring organisations - working in partnership, often at a local level. Significantly, the European Commission recognises the benefits of such processes and stresses the social outcomes that these can deliver, noting that, “implementing GI features in urban areas creates a greater sense of community, strengthens the link with voluntary actions undertaken by civil society, and helps combat social exclusion and isolation. They benefit the individual and the community physically, psychologically, emotionally and socio-economically”. The Aachen City Region was selected as suitable study area for this purpose given its prominent position at the “heart of Europe”, on the border of Germany, Belgium and the Netherlands, its range of geographical zones, habitat types and its diverse patterns of population distribution. For the purposes of comparison and for providing additional insights, additional case study examples from Scotland were also incorporated into the study at a later stage. Scotland has a strong tradition of community greenspace management, volunteering and citizen engagement within the natural resources sector. In contrast to Germany, Scotland has actively pursued high level legislation and mainstreaming of governmental polices which aim to promote and facilitate direct participation in GI and land management by local citizens’ groups. This makes it a valuable example for the purposes of contrasting and comparison. At a practical level, the Study aimed to identify and define the extent of GI network in the Aachen City Region and then to research and collate examples of citizen participation within the Study Region through desk based research, insider expert knowledge and evidence from the field. These processes resulted in the selection and identification of detailed case studies. These were aligned along a transect which represented rural, peri-urban and urban areas of the Städteregion Aachen. Interviews with local residents and stakeholder groups were undertaken within each of the case study areas. Through use of a comparison Framework and SWOT analysis of the selected case studies, key positive and negative learning points were identified from each location. Similarly, a lesser number of case studies were identified from Central Scotland for comparison purposes, using existing officially documented examples of citizen participation. A similar process of detailed evaluation was then also undertaken for each of the identified Scottish case study examples. Through these processes a series of policy guidelines were formulated and grouped under 14 key headings. These aimed at improving support structures available to local citizens groups from statutory authorities and mentoring bodies through proposing a series of practical reforms to policy, funding streams and delivery structures. These also included a number of keystone measures; in particular the creation and development of a strategic GI partnership structure for the Städteregion Aachen to enhance the interface and thematic links between top-down policy driven approaches and bottom-up citizen led actions. Consideration was made as to the practicality of implementing these measures through stakeholder dialogue. Obtaining such stakeholder feedback became more difficult in the later stages of the research due to the impacts of the Corona Pandemic. Final conclusions consider more generally at a more conceptual level, the drivers of change needed to facilitate the processes of bottom up, citizen led participation through bringing about institutional change within statutory bodies and mentoring organisations and their associated interactions with local citizens’ groups. The practical extent to which such approaches might be applied and promulgated across borders to deliver multifunctional GI outcomes is given consideration given the extent of local cultural, administrative and fiscal influences.
Keywords: Stadtgrün; Grünflächenplanung; Stadtgestaltung; Freiraumgestaltung; Infrastrukturentwicklung; Planungsbeteiligung; Bürgerbeteiligung; Partizipation; Fallstudie; Vergleichsuntersuchung; Grüne Infrastruktur